Surgical Treatment of Dysphagia Lusoria Caused by Right-Aortic Arch with Kommerell Diverticulum: Left Heart Bypass without Subclavian Revascularization - Camporrotondo, Mariano; Ricapito, Paz; Espinoza, Juan Carlos; Piccinini, Fernando; Vrancic, Mariano; Avegliano, Gustavo; Navia, Daniel (AORTA, 2018)
The authors present the case of a 26-year-old patient suffering from dysphagia because of compression by a Kommerell diverticulum in right aortic arch anomaly. Open surgical arch and descending aorta replacement with left heart bypass without left subclavian artery reimplantation was performed.
Keywords: right aortic arch; dysphagia lusoria; Kommerell diverticulum